Flexible exchange rate regimes in emerging markets: Current insights and avenues for future research - Moutaib Nouhaila; Lahrichi Younès (Global Business & Finance Review (GBFR), 2023)
Purpose: Providing a structured literature review on the flexiblization of exchange rate regime in emerging countries with a focus on recent studies conducted in the field, in order to identify promising opportunities of future research. Design/methodology/approach: Starting with a review of the International Monetary System (IMS) evolution before addressing the theoretical corpus related to exchange rate regimes, before shedding the light on the main types of exchange regimes. Then, reviewing the main studies published between 2000 and 2023. Findings: The more we deepen the research in the field, the more we realize that the literature has not given enough interest to study the impact of exchange rate regime flexiblization on the microeconomic level, especially on companies. Indeed, it would be interesting to study the impact of exchange rate regimes flexiblization on companies mainly through financial performance indicators, e.g., solvency, turnover and financial profitability. Research limitations/implications: The limitations of this study are the few even missing work studies done on the micro economic level to deeply analyze the aspects of this shutter. Originality/value: The originality of this work is to have a critical analysis of the existing knowledge body and current contributions in the field in order to identify potential further unexplored aspects such as studying the impact of exchange rate regime on firms, on the micro economic level, which is an area not exploited in literature. A better understanding of the impact on companies' profitability could benefit more practitioners as well as policymakers to more likely frame and control the process of floating their local currency.
Keywords: 650; Exchange rate regime; Flexiblization; Emerging countries; MENA region; Literature review; International monetary fund